Stokes shift and band gap bowing in InxGa1-xN (0.060?x?0.105) grown by metalorganic vapour phase epitaxy - Yildiz, A.; Dagdelen, F.; Acar, S.; Lisesivdin, S. B.; Kasap, M.; Aydogdu, Y.; Bosi, M. (Polish Acad Sciences Inst Physics, 2008)
We presented the results of electrical and optical studies of the properties of InxGa1-xN epitaxial layers (0.060 <= x <= 0.105) grown by metalorganic vapour phase epitaxy. Resistivity and Hall effect measurements of the samples were carried out at room temperature. Optical properties of the samples were characterized by photoluminescence and optical absorption spectroscopy. The comparison between the photoluminescence and the optical absorption measurements gives the Stokes shift. We explained the observed Stokes shift in terms of Burstein-Moss effect. The band gap versus composition plot for InxGa1-xN alloys is well fitted with a bowing parameter of approximate to 3.6 eV.
Conference on New Materials for Magnetoelectronics - MAG-EL-MAT -- MAY 07-10, 2007 -- Bedlewo, POLAND
Keywords: Optical-Properties; Ingan Epilayers; Alloys; Films; Deposition; Layers; Thick